Endoscopic therapy of anastomotic diverticulum combined with stercorolith incarceration: A case report - Liu, Yi; Chen, Zhihao; Dou, Lizhou; Liu, Siyao; Zhang, Yueming; Liu, Yong; Wang, Guiqi (Frontiers in Medicine, 2022)
Diverticulosis is a commonly acquired disease of the lower gastrointestinal tract, which may be associated with significant morbidity and adverse effects on quality of life. Although several national guidelines focused on the treatment of diverticulosis, multiple controversies remained regarding the disease management of diverticulosis. For some controversial issues, such as the role of antibiotics in mild diverticulitis, when and how to operate on patients with acute diverticulitis, there is no conclusion yet. To our knowledge, this is the first report of endoscopic therapy for anastomotic diverticulitis caused by stercorolith incarceration. In the current case, a 49-year-old woman complained of recurrent subumbilical pain without obvious inducement for half a year. Colonoscopy showed anastomotic diverticulum combined with stercorolith incarceration. After local inflammation relieved by conservative treatment, the patients received endoscopic mucosal incision and lithotomy. Then the diverticulum was closed with titanium clips. The abdominal pain of patient was completely relieved, and the reexamination of colonoscopy showed that the wound healed well after 1 year of follow-up. This case suggests that for anastomotic diverticulitis caused by stercorolith incarceration, endoscopic therapy can remove the stimulation factors better and avoid the recurrence and progression of the disease compared with conservative treatment. Moreover, endoscopic therapy achieves the maximum in minimally invasive surgery and reduces complications and surgical costs compared with radical surgery.